Long-Term Efficacy and Safety of Subconjunctival/Perilesional 5-Fluorouracil Injections for Ocular Surface Squamous Neoplasia - Sun, Yuzhao (Drug Des Devel Ther, 2020)
PURPOSE: To investigate the effectiveness and safety of subconjunctival/perilesional 5-fluorouracil injections on ocular surface squamous neoplasia (OSSN) during a 3-year follow-up period. PATIENTS AND METHODS: We followed up six patients with intraepithelial OSSN (in one eye each) that had regressed after subconjunctival/perilesional 5-fluorouracil injections. Conjunctival fluorescein angiography (FA) and indocyanine green angiography (ICGA), as well as anterior segment optical coherence tomography (AS-OCT), were performed to evaluate the OSSN status 3 years after initiation of treatment. RESULTS: The mean age of patients (five males, one female) at baseline was 62.3±11.6 years. The mean number of 5-fluorouracil injections was 17.0±8.6, with a mean treatment duration of 13.0±7.4 weeks. At the final visit, both intratumoral and conjunctival feeding vessels had disappeared on ICGA and FA, with no neovascularization-related leakage, in accordance with the results of AS-OCT. The period from complete tumor regression to final visit according to AS-OCT was 32.5±4.2 months, which was longer than that according to ICGA (31.3±3.2 months, p=0.034). The final best-corrected visual acuity was similar to that at baseline (p=0.128). No side effects were observed in any of the eyes. CONCLUSION: Subconjunctival/perilesional 5-fluorouracil injections are an effective and safe treatment for OSSN. Future studies with a larger sample size are warranted for confirmation of our findings, as well as investigation into the reasons for residual areas of non-perfusion in the conjunctiva.